Stretching Life Out, Maintaining the Body. Part I: Vayas in Medical Literature - Barois, Christèle (History of Science in South Asia)

(untitled) (University of Alberta Library, 2017)
The representation of the process of human life is at the heart of questions about longevity, rejuvenation practices and possibly those which aim at immortality. The key term for “age” in medieval India is vayas, which means “vigour”, “youth” or even “any period of life”, that is to say exactly the same meaning as ours (duration of life). As a criterion for the examination of the patient, vayas is invariably divided into three periods: childhood, intermediate age and old age, precisely defined in the ayurvedic saṃhitās. It seems that vayas might be a relevant gateway to the cross-disciplinary understandings of age in medieval India, and therefore to the conditions of its (relative) mastery.